SEARCH FOR NEW GAUGE BOSONS DECAYING INTO DIELECTRONS IN (P)OVER-BAR-P COLLISIONS AT ROOT-S=1.8 TEV - Abe, F; Albrow, M; Amidei, D; Antos, J; Anwaywiese, C; Apollinari, G; Areti, H; Atac, M; Auchincloss, P; Azfar, F; Azzi, P; Bacchetta, N; et al. (1995)
We have searched for heavy neutral gauge bosons (Z') in p̄p collisions at s=1.8 TeV. The data were obtained using the CDF detector during the 1992-1993 run corresponding to an integrated luminosity of 19.7±0.7 pb-1. We present a 95% confidence level upper limit on the production cross section times the branching ratio of Z' decaying into dielectrons as a function of Z' mass. Assuming standard model coupling strengths, we exclude a Z' with a mass less than 505 GeV/c2. We also present lower mass limits for Z' bosons from E6 models and the alternative left-right model. © 1995 The American Physical Society.